The Roles of Advocate Professional Education in Improving the Quality and Competitiveness of Sharia and Law Alumni - Rahman Syamsuddin; Abd Rais Asmar (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2022)
This study aimed to determine the quality and competitiveness improvement of alumni of the Faculty of Sharia and Law (FSH), Alauddin State Islamic University Makassar (UINAM), through the Special Advocates Professional Education (PKPA). The method uses a normative juridical approach with quantitative data collection using surveys. The results show an increase in the quality of alumni after participating in PKPA from the aspect of graduate user satisfaction, such as law offices, state institutions, and the private sector. The quality of PKPA UINAM as a printer of advocates also increases periodically as well as the enthusiasts of participants. Following that, the competitiveness shown by the short waiting period of work, which is 3.5 months, and the contribution graduates, who can contribute as much as 15% of the total national Advocate Profession Exam (UPA) participants. It shows the implications given by making the competitiveness of alumni able to compete nationally and globally.